PENERAPAN FUZZY C – MEANS MEMPREDIKSI KEUNTUNGAN DAN PAJAK CUKAI PENJUALAN ROKOK BERDASARKAN KELOMPOK PENGGUNA ROKOK DAN TEMBAKAU - Tia Rizkika; Dicky Apdillah (Smart Education, 2025)
Abstract: The cigarette industry is a sector that contributes significantly to state revenue through taxes and excise. This study aims to apply the Fuzzy C-Means method to cluster cigarette consumption and sales data to predict potential sales profits and projected excise revenues. The data used is secondary data obtained from the Central Statistics Agency (BPS) and the Ministry of Finance. The research process includes data collection, pre-processing, analysis using the Fuzzy C-Means algorithm, and implementation of a web-based system using PHP and MySQL. The results show that the Fuzzy C-Means method is capable of grouping cigarette consumption data into several clusters, such as